Economic value of community forest to local users : A case study from Barandabhar Protected Forest, Chitwan, Nepal - Lamichhane, R.; Sedhain, A.; Maharjan, M. (Banko Janakari, 2019)
Barandabhar Protected Forest (PF) has provided numerous goods and services to the people living around the forest. Integrated evaluation of this PF along with its ecological and economic value is required for the conservation and sustainable management of its forest resource. The field study was carried out in two community-managed forests around the Barandabhar PF Market Price Method and Contingent Valuation Method were used to estimate the use and non-use values of the forest. Determination of the local users' willingness to pay for sustainable management and conservation of the natural resources was done through Contingent Valuation Survey. It was administered to 142 users. Multiple Regression Model was used to analyze the factors affecting the users' willingness to pay (WTP) value. The WTP value for the conservation and sustainable management of forest was found to be affected by the income and gender of the users and their time to reach the forest. The study revealed that the women were more willing to pay for the environmental services provided by the forest. Based on the household (HH) survey, the average HH-consumption of the forest products (timber, fodder and fuelwood) was estimated to be worth of NRs. 5,246 (US 46. 69) per HH per year and the specific use value of the forest was estimated to be NRs. 15,160,940 (US134,931. 82) per year. The total WTP value for the sustainable management and conservation of the forests was estimated to be NRs. 1,341,153 (US11,936. 20) per year; the users' average WTP value for the conservation and sustainable management of the Barandabhar PF being NRs. 589 (US 5. 24) per HH per year.